The State of Current Value Accounting. - Edwards, Edgar O. (The Accounting Review, 1975)
The demonstrated and likely volatility of prices during this decade suggests a review of current value accounting is in order, as of April 1975. The literature indicates a substantial acceptance of current value accounting in accounting theory, but an impressive lack of implementation in accounting practice. What has been less widely discussed, both in the media and the professional literature, is the outlook for differential price changes, for changes in relative prices. The author says that over the next five years the principal economic and accounting challenge will come from substantial and pervasive shifts in relative prices. For example, between 1972 and 1973, while the wholesale price index in the U.S. was rising by 13.8%, the farm products and processed foods and feeds portion of it rose by 30% and the industrial commodities portion by only 7.7%, a difference in rate of increase of 22.3 percentage points. In this article the author also brings out some of the conceptual issues involved in current value accounting, then he discusses some of the valuation issues, and finally identifies some of the potential analytical uses of current value data.